Hereditary angioedema: a bradykinin-mediated swelling disorder - Björkqvist, Jenny; Sala-Cunill, Anna; Renné, Thomas (Thrombosis and Haemostasis, 2013)
Edema is tissue swelling and is a common symptom in a variety of diseases. Edema form due to accumulation of fluids, either through reduced drainage or increased vascular permeability. There are multiple vascular signalling pathways that regulate vessel permeability. An important mediator that increases vascular leak is the peptide hormone bradykinin, which is the principal agent in the swelling disorder hereditary angioedema. The disease is autosomal dominant inherited and presents clinically with recurrent episodes of acute swelling that can be life-threatening involving the skin, the oropharyngeal, laryngeal, and gastrointestinal mucosa. Three different types of hereditary angiodema exist in patients. The review summarises current knowledge on the pathophysiology of hereditary angiodema and focuses on recent experimental and pharmacological findings that have led to a better understanding and new treatments for the disease.
Keywords: Contact phase; inflammatory mediators; proteases; SERPINs